A Model of Teacher Leadership in History Instruction - Chutimant, Poramatdha (Scholar: Human Sciences, 2015)
Education has played an important role in creating development for the country and enhancing new knowledge and perspectives for people by studying the core details of each course. Education is also counted as a key aspect in creating the quality of a being human. This means that education reveals the characteristics and performance of humans at their best.